Mathematical Problem-Solving Abilities with a Metacognitive Approach at High School Students - Amelia, Dini Okta; Rosyadi, Alfiani; In'am, Akhsanul (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2025)
Problem solving is a sequence of mental processes for resolving an issue varying from comprehending the problem to reassessing the outcomes of addressing the problem. This research aimed to explore mathematical problem-solving examined through students' metacognitive capacities. This investigation is a descriptive study using a qualitative method. The participants in this research were students of the 10th grade of Maarif Lawang High School, comprising 6 individuals. Data gathering methods in the shape of assessments and paired discussions. Data interpretation methods are carried out through data collection, data compression, data display, and inference drawing. The findings revealed that learners in the high category fulfilled all signs ranging from the first to the fourth, and learners in the moderate categories fulfilled one to three signs on each query. In contrast, learners in the low category only met one distinct sign on each provided query. The inference is that learners in the high category fulfill all metacognitive signs, learners in the moderate category fulfill only three signs, and learners in the low category fulfill various signs. Recommendations for future researchers are encouraged to conduct further investigations with progressively extensive and diverse participants to ensure the acquired information is more comprehensive.